Seeing in special ways : children living with blindness - Bergman, Thomas, 1947- (Milwaukee : Gareth Stevens Children$1 (Bs Books,s, 1989)
Interviews with a group of blind and partially sighted children in Sweden reveal their feelings about their disability and the ways they use their other senses to help them "see."
Translation of: Fingrar som ser.
Includes bibliographical references (p. 52).
Keywords: Blind children -- Juvenile literature; Blind; People with visual disabilities; People with disabilities